Between violence and justice: the act of judging in the light of Paul Ricoeur's philosophical anthropology - Pires Guedes, Maurício; Neves Justino, Lucas (Ius Humani. Jornal do direito, 2025)
Based on the central concepts of narrative identity and institutional mediation, the text addresses the notion of the subject of rights according to Paul Ricoeur, highlighting its dynamic nature and the multiple elements that shape its identity. Ricoeur proposes that the subject of rights goes beyond a simple legal construction, being grounded in the articulation between autonomy and vulnerability. This duality underscores the importance of narrative identity, in which personal history is continuously built and modified, enabling the individual to understand themselves and to be recognized within the legal order. The personal narrative, embedded in the symbolic orders of law, is considered an essential element for the subject to act not merely as a bystander but as a protagonist in their own journey. However, the development of these capacities depends on institutional mediation, which facilitates the transformation of the subject's potential into effective rights. This mediation establishes a dialogical environment that fosters the active participation of the parties in the judicial process, contributing to decisions that reflect mutual understanding and promote justice. Moreover, the text discusses the act of judging, emphasizing that the performance of the judiciary should go beyond the formal application of norms. By creating a space for reciprocal interaction, the judiciary legitimizes its role as mediator, allowing the judicial decision to emerge from a thorough analysis of the arguments and narratives presented, thereby reinforcing the recognition of subjects and the consolidation of a just and peaceful society.